Total Synthesis and Biological Evaluation of the Glycosylated Macrocyclic Antibiotic Mangrolide A. (18th July 2018) - Hattori, Hiromu; Roesslein, Joel; Caspers, Patrick; Zerbe, Katja; Miyatake‐Ondozabal, Hideki; Ritz, Daniel; Rueedi, Georg; Gademann, Karl
Abstract: The macrocyclic antibiotic mangrolide A has been described to exhibit potent activity against a number of clinically important Gram‐negative pathogens. Reported is the first enantioselective total synthesis of mangrolide A and derivatives. Salient features of this synthesis include a highly convergent macrocycle preparation, stereoselective synthesis of the disaccharide moiety, and two β‐selective glycosylations. The synthesis of mangrolide A and its analogues enabled the re‐examination of its activity against bacterial pathogens, and only minimal activity was observed.